Persepsi Masyarakat terhadap Stunting di Kabupaten Majene Sulawesi Barat (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2022)
Stunting is a form of stunted growth process and is a nutritional problem that needs attention and is one of the main public health problems in Indonesia. Parenting is one of the factors that can cause nutritional problems such as stunting because toddlers still depend on the parenting applied by the family in fulfilling their food and health care. This study aims to determine public perceptions of stunting in three villages in the Pamboang Health Center working area consisting of North Bonde Village, Banua Adolang Village and Betteng Village which are included in the village with the highest number of stunting rates in Majene Regency. This study uses a qualitative approach which was carried out from December 2020 to January 2021 by conducting in-depth interviews, observations with a total of 6 mothers who have stunting status of toddlers. The results of this study indicate that stunting is not only a measure of short height, but rather on the concept that the process coincides with the process of growth and development inhibition by linking the developmental parameters of toddlers through DDST and KBK. The results of interviews in the field are relevant to the theory so that the results of public perception assume that stunting is a fact that exists in the community so that it can have an impact on optimal community involvement in an effort to encourage the government to reduce stunting.